PENGARUH LITERASI KEUANGAN, PERENCANAAN KEUANGAN, PERILAKU KEUANGAN, DAN INKLUSI KEUANGAN TERHADAP KESEJAHTERAAN KEUANGAN PELAKU UMKM DI KECAMATAN TEBING TINGGI KABUPATEN KEPULAUAN MERANTI - Ariza Ifan; Kamaliah Kamaliah; Aunurrafiq Aunurrafiq (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
Financial literacy is financial knowledge and capability that affects efforts toimprove financial well-being (Hidayah et al., 2021). This study aims to examineand analyze the effect of financial literacy, financial planning, financial behavior,and financial inclusion on financial well-being. This research includesquantitative research. The total population in this study was 1,384 SMEs in thedistrict. High Cliffs, Meranti Islands Regency. The sampling method used in thisstudy is non-probability sampling with the side quota method. This research wascollected through a survey by distributing questionnaires, where the respondentsconsisted of SMEs in the district. Tebing Tinggi, Meranti Islands Regency, whichis in the trade, service provider, and food/beverage processing sector with a totalof 200 respondents. The data were analyzed using multiple regression methodusing SPSS version 26. The results of the study prove that financial literacy,financial planning, financial behavior, and financial inclusion on financialwelfare. Keywords: Financial Literacy, Financial Planning, Financial Behavior, FinancialInclusion, and Financial Welfare.